Biomarkers of Proteolytic Damage Following Traumatic Brain Injury - Pineda, Jose A. (Brain Pathol, 2006)
The history of numerous failed clinical trials designed to identify therapeutic agents to assist in improving outcomes after traumatic brain injury points to the critical importance of understanding biochemical markers of injury. Such biomarkers should be readily accessible, provide information specific to the pathologic disruptions occurring in the central nervous system, and allow improved monitoring of the progression of secondary damage. Additionally, these biomarkers should may provide investigators a window on the individual patient's response to treatment, and should contribute to prediction of outcome. Most research on this topic to date has focused on neuron‐specific enolase (NSE) and S‐100 proteins but these have not proven to be satisfactory for a variety of reasons. A different approach is provided by the study of 2 important proteases, caspase‐3 and calpain. This paper reports the current state of knowledge concerning caspase and calpain as specific markers of TBI, and discusses alll‐spectrin, a principal substrate for both caspase and calpain, as well as initial findings regarding neurofilament 68 protein (NF‐68).